2011
DOI: 10.1002/jqs.1488
|View full text |Cite
|
Sign up to set email alerts
|

Alkenones and coccoliths in ice‐rafted debris during the Last Glacial Maximum in the North Atlantic: implications for the use of UK37′ as a sea surface temperature proxy

Abstract: The U K 37 0 index has proven to be a robust proxy to estimate past sea surface temperatures (SSTs) over a range of time scales, but like any other proxy, it has uncertainties. For instance, in reconstructions of the Last Glacial Maximum (LGM) in the northern North Atlantic, U K 37 0 indicates higher temperatures than those derived from foraminiferal proxies. Here we evaluate whether such warm glacial estimates are caused by the advection of reworked alkenones in ice-rafted debris (IRD) to deep-sea sediments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…It is nonetheless worth noting that chlorins were detected in GDF samples from the North Sea Fan and Svalbard depocenter while absent from any other GDF sediments analyzed here (see supporting information Figure S2). Interestingly, the presence of alkenones was also reported in GDF sediments from these two depocenters (Rosell‐Melé et al, 2011). The occurrence of these compounds in marine sediments is usually attributed to autochthonous inputs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is nonetheless worth noting that chlorins were detected in GDF samples from the North Sea Fan and Svalbard depocenter while absent from any other GDF sediments analyzed here (see supporting information Figure S2). Interestingly, the presence of alkenones was also reported in GDF sediments from these two depocenters (Rosell‐Melé et al, 2011). The occurrence of these compounds in marine sediments is usually attributed to autochthonous inputs.…”
Section: Discussionsupporting
confidence: 56%
“…The reader is referred to the supporting information from Rosell‐Melé et al (2011; https://onlinelibrary.wiley.com/doi/abs/10.1002/jqs.1488) for further description of these trough‐mouth fans and the corresponding analyzed cores.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Rosell‐Melé et al . [] demonstrated that the input of reworked alkenones by IRD in the North Atlantic does not necessarily lead to higher alkenone‐based SSTs in marine sediments. Finally, during older glacials, ice‐rafting events at Site U1313 are always accompanied by abrupt cooling episodes [ Stein et al ., ; Naafs et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…(2011) show that during the last glacial there can be different temperature trends as represented by different marine proxies. This is certainly something to be mindful of and forms an extensive and current area of research during this period (Rosell‐Melé et al ., 2011). We selected all sites where the original authors considered the temperature estimates of annual temperature to be reliable.…”
Section: Sea Surface Temperature Reconstructionsmentioning
confidence: 99%